أضواء حول مراكز العلم والثقافة في العصر العباسي الأول (132-232 هـ/ 749-846 م) (Comprehensive Journal of Science, 2025)
The research Sheds light on the centers of science and culture in the early Abbasid Era (132-232 AH /749-846 AD) and their effective impact in keeping pace with the times, with their constant commitment , that is, the scientific centers, to caring for Scholars and student of knowledge, and developing their Curricula alike, and clarifying the role of Statesmen, including caliphs and Others, in Supporting these Scientific centers, which formed the intellectual foundation upon which the vehicle of the Islamic nation's Renaissance was based in all its aspects.
Keywords: Scientific centers, kuttabs,mosques, booksellers, Abbasid caliphs, the desert.